PENINGKATAN LITERASI DIGITAL MAHASISWA MELALUI PELATIHAN DIGITAL MARKETING DAN PEMBUATAN PERENCANAAN KONTEN SOSIAL MEDIA DI UNIVERSITAS PATOMPO MAKASSAR - Febisatria, Andhi; Eureka Tri zarazwaty; Abd. Rahman Yus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Advances in digital technology have shifted marketing strategies and require students to develop digital marketing skills. Students of the Management Study Program at Patompo University still show limited understanding of digital strategies and content planning. This community service program aims to strengthen digital literacy through digital marketing training and mentoring in content planning. The activity was conducted on August 28, 2025, at the Faculty of Economics Auditorium, Patompo University. The results show improved student abilities in designing digital strategies, producing structured content, and using social media for promotional purposes. The program enhances students’ practical readiness for digital-based industry demands.